Human Development Index And Employment Provision In Medan City - Raynaldo, Raynaldo (Publisher Cv. Inara, 2022)
This study aims to analyze the effect of economic growth and the number of industries on the provision of employment in the city of Medan. Where there are two dependent variables, namely the human development index and employment. There are five independent variables, namely GRDP, number of industries, population, wages and local revenue. This study uses secondary data or time series, namely from 2015 to 2021. The data analysis model in this study uses the Simultaneous Regression method. There is one variable for simultaneous results that shows an effect on the human development index, namely GRDP and has a positive and significant effect on the human development index. For the effect on employment, there are two variables for simultaneous results that show the effect on employment, namely the number of residents has a negative and significant effect on employment and wages have a positive and significant effect on employment.